腭裂相关基因甲状腺转录因子-2转基因小鼠的生物学特征 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2014)
OBJECTIVE: The aim of this study is to establish a transgenic mouse model for cleft palate relevant gene thyroid transcription factor-2 (TTF-2), which can be used to study palatal shelf development when the expression pattern and regular activation of TTF-2 is altered. METHODS: The C57BL/6J mouse TTF-2 gene was cloned through polymerase chain reaction (PCR) from the mouse genomic DNA. The TTF-2 gene was inserted into the expression vector pBROAD3-mcs to construct the recombinant expression vector pBROAD3-TTF-2. This expression vector was then microinjected into the male pronuclei of the fertilized mouse ovum. Thus, the TTF-2 transgenic mice model was established. The genotype of the transgenic mice was identified by PCR and Southern blot analysis. Immunohistochemistry identified the consistent expression of TTF-2 gene during its palatal shelf development. RESULTS: TTF-2 genes were microinjected into 982 fertilized ova. A total of 580 two-cell-stage embryos cultured and transplanted into the oviducts of 48 pseudopregnant female mice. Overall, 68 embryos were obtained for analysis. The genotype of the mice was determined through PCR and Southern blot analysis using genomic DNA extracted from tail biopsies of the transgenic fetus. A total of 13 TTF-2 transgenic mice were detected. The expression of TTF-2 gene during the palatal shelf development of the transgenic mice was consistently detected by immunohistochemistry. CONCLUSION: The recombinant expression vector pBROAD3-TTF-2 was integrated into mouse genome through microinjection. The transgenic mouse in the palatal shelf that consistently expressed TTF-2 was successfully established and displayed a cleft palate phenotype.